2018
DOI: 10.1515/jpm-2016-0371
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound in the prediction of birth weight discordance in twin pregnancies: are we there yet?

Abstract: The accuracy of ultrasound in the prediction of BWD is limited, particularly in pregnancies without fetal growth restriction. Clinical decisions should not rely on BWD alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Conversely, other studies have found that secondtrimester ultrasound discordance in twins has poor predictive value for adverse perinatal outcomes, irrespective of chorionicity [1,[18][19][20]. Although in some investigations, second-trimester EFW discordance correlated with birth-weight discordance ≥20-25%, the predictive accuracy was low, thus preventing its wide practical clinical use [7,8].…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, other studies have found that secondtrimester ultrasound discordance in twins has poor predictive value for adverse perinatal outcomes, irrespective of chorionicity [1,[18][19][20]. Although in some investigations, second-trimester EFW discordance correlated with birth-weight discordance ≥20-25%, the predictive accuracy was low, thus preventing its wide practical clinical use [7,8].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the risk is further increased in twin pregnancies with birthweight (BW) discordance [2][3][4]. Intertwin BW discordance has various definitions, but most commonly it is expressed as an intertwin BW difference ≥ 20 % relative to the larger twin [2,[4][5][6][7][8], and it occurs in approximately 16 % of all twin pregnancies [4].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These methods have been extensively studied throughout the last decades. The majority of publications have reached the conclusion of poor sensitivity in predicting intertwin BW discordance [5,6,[9][10][11][12][13], however the performance is better when performed near delivery [7,8,[13][14][15]. Recently, Hehir et al [13] investigated the performance of ultrasound EFW in predicting intertwin BW discordance at different gestational ages.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In this systematic review, we attempted to address the problem by creating different growth restriction groups so as to be as inclusive as possible. (78). However, most studies in our search that reported growth based on postnatal measures used BWD as opposed to LBW, therefore it was decided to include BWD in our systematic review.…”
Section: Accepted Manuscriptmentioning
confidence: 99%